Principles and values in criminal law and criminal justice essays in honour of Andrew Ashworth - Roberts, Julian V.; Zedner, Lucia; Ashworth, Andrew (Oxford : Oxford University Press, 2012)
Celebrating one of the leading lawyers of the common law, Andrew Ashworth, the essays in this volume address fundamental questions of principle and value in criminal law, criminal process, human rights, sentencing, and punishment. This is a contribution to contemporary debates about criminalisation and punishment.
Description based on online resource; title from PDF title page (viewed on Aug. 24, 2012).
Includes bibliographical references and index.
Keywords: Criminal law -- Philosophy; Human rights; Punishment